2011
DOI: 10.1155/2011/840194
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Retinoid X Receptor Ligand in the Anti-Inflammatory Effect Induced by Peroxisome Proliferator-Activated Receptor Agonist In Vivo

Abstract: Peroxisome proliferator-activated receptor γ (PPARγ) forms a heterodimeric DNA-binding complex with retinoid X receptors (RXRs). It has been reported that the effect of the PPAR agonist is reduced in hepatocyte RXR-deficient mice. Therefore, it is suggested that the endogenous RXR ligand is involved in the PPARγ agonist-induced anti-inflammatory effect. However, the participation of the RXR ligand in the PPARγ-induced anti-inflammatory effect is unknown. Here, we investigated the influence of RXR antagonist on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…However, it has been described that an ophthalmic solution containing 0.1% PGZ inhibited inflammation, decreased the fibrotic reaction, and prevented corneal neovascularization in the cornea from the early phase after alkali burn injury in rats (4). However, in another study, it was shown that the PGZ inhibited intraocular concentrations of TNF-α and IL-6 in the endogenous uveitis model (2). These results demonstrated that PPARγ agonists may represent a way of moving forward with a treatment strategy focused on clinical applications in inflammatory processes and better wound healing.…”
Section: In Vivo Anti-inflammatory Efficacymentioning
confidence: 93%
See 2 more Smart Citations
“…However, it has been described that an ophthalmic solution containing 0.1% PGZ inhibited inflammation, decreased the fibrotic reaction, and prevented corneal neovascularization in the cornea from the early phase after alkali burn injury in rats (4). However, in another study, it was shown that the PGZ inhibited intraocular concentrations of TNF-α and IL-6 in the endogenous uveitis model (2). These results demonstrated that PPARγ agonists may represent a way of moving forward with a treatment strategy focused on clinical applications in inflammatory processes and better wound healing.…”
Section: In Vivo Anti-inflammatory Efficacymentioning
confidence: 93%
“…antifibrotic, anti-tumor effects, and neuroprotection. Moreover , it has a protective effect on inflammatory ocular process (1)(2)(3)(4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A significant negative correlation was found between PPARγ1 and edema. The expression levels of both PPAR and RXR mRNA have been found to be decreased in animal model with liver inflammation, indicating that PPARγ and RXR agonists may play an important role in response to inflammation and fibrosis (28).…”
Section: Rat Muscle Of Nimesulide Group Showing Mild (+) To Moderamentioning
confidence: 99%
“…The PPARγ receptors have various functions including anti-angiogenic, antifibrotic, anti-inflammatory and anti-tumor effects. [7][8][9][10] PGZ is also neuroprotective in models of neurodegenerative disorders, 10 highlighting PPARγ agonists as a promising treatment for AD. 11 Thus, PGZ has been reported to reduce oxidative stress, normalize cerebral blood flow and glucose uptake, increase neuronal activity and exert positive effects on cerebrovascular functions in an animal model of AD.…”
Section: Introductionmentioning
confidence: 99%